Doping of Calcium of Hydroxide on Bio-adsorbent for Removal of Fluoride from Water - Dr. A.D.Kulkarni, Snehal Thorat1, KavitaKulkarni, (International Journal of Scientific Research and Management (IJSRM), 2017)
Fluoride is one of the anionic contaminants, whichis found in excess in surface or groundwater because of geochemical reaction or anthropogenic activities such as the disposal of industrial wastewater. Biodsorbent-Butea-Monosperma leaf powder was prepared by doping of calcium hydroxide in the microwave. A batch study on fluoride biosorption was carried out for different variables, like  pH, initial fluoride concentration, dose of adsorbent, of horizontal shaker.In order to investigate the mechanism of fluoride removal, various adsorption isotherms such as Langmuir and Freundlich were studied